Transition of Long-Term Care in Hungary: Problems and Solutions - Széman, Zsuzsa (European Journal of Mental Health, 2015)
Problems and Solutions: The study presents the challenges of long-term care for the elderly from 1993 to the present, which arise from the poor state of health of the population over 65. It analyses the related trend in policy on the elderly, how a positive trend up to 2008 took a negative turn. Against this background, it examines the role family carers play in caregiving. Their task has become increasingly difficult as a result of the state shifting responsibility to the families, strong demographic ageing and the appearance of declining health in an early stage of the life cycle. Alternative solutions must be found to relieve this burden, and one possible direction is the incorporation of ICT into long-term care. The study presents innovative solutions facilitating care: the WebNurse developed for family carers and Skype Care to ease the loneliness of the elderly.